Effect of the Kahoot-Assisted Team Games Tournament Model on Mathematics Learning Outcomes of Grade XI Students - Intan Puspita Devi; Novi Mayasari; Ari Indriani (Journal of Mathematics Education and Science, 2025)
The low learning outcomes of students, especially in mathematics learning, indicate the need to implement innovative learning models. This study aims to determine the effect of implementing the Team Games Tournament learning model with the help of Kahoot on the mathematics learning outcomes of XI grade students of SMA Negeri 1 Balen, especially on the tangent circle. This research is included in the quasi-experimental model by applying the cluster random sampling technique. This study included grade XI students at SMA Negeri 1 Balen in the 2024/2025 school year as the research population, comprising six classes with 206 students. Class XI-1 (experimental class) and class XI-2 (control class) were selected as the research samples. Test and documentation were chosen as the research data collection techniques. Based on the t-test results with alpha = 5% and DK =   the obtained tcount = 3.251. Because the tcount] falls within the critical region (DK), H0 is rejected and H1 is accepted. The data analysis shows an influence in implementing the Team Games Tournament (TGT) model on the learning outcomes of grade XI students on the circle tangent at SMA Negeri 1 Balen. The average posttest score for students in the experimental class was 84.056, whereas it was 77.706 in the control class it was 77.706, further confirming the positive influence of this learning model. Practically, the results of this study can be used as an alternative learning strategy for educators to increase active participation and student learning outcomes.